2013
DOI: 10.1111/tra.12136
|View full text |Cite
|
Sign up to set email alerts
|

The Vps35 D620N Mutation Linked to Parkinson's Disease Disrupts the Cargo Sorting Function of Retromer

Abstract: The retromer is a trimeric cargo-recognition protein complex composed of Vps26, Vps29 and Vps35 associated with protein trafficking within endosomes. Recently, a pathogenic point mutation within the Vps35 subunit (D620N) was linked to the manifestation of Parkinson's disease (PD). Here, we investigated details underlying the molecular mechanism by which the D620N mutation in Vps35 modulates retromer function, including examination of retromer's subcellular localization and its capacity to sort cargo. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
247
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 207 publications
(262 citation statements)
references
References 47 publications
(78 reference statements)
12
247
2
1
Order By: Relevance
“…Mutations in VPS35, VPS26A and the retromer accessory protein DNAJC13 [43][44][45][46] have been associated with late-onset autosomal dominant Parkinson's disease (PD) [47][48][49][50]. Indeed, the PD-linked VPS35(p.D620N) mutation displays a reduced ability to associate with the actin polymerizing WASH (Wiskott-Aldrich syndrome protein and SCAR Homology) complex [51][52][53] which leads to altered endosome-to-Golgi transport and autophagosome formation [54,44,55,56]. Perturbed function of the WASH complex is also implicated in hereditary spastic paraplegia [57].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in VPS35, VPS26A and the retromer accessory protein DNAJC13 [43][44][45][46] have been associated with late-onset autosomal dominant Parkinson's disease (PD) [47][48][49][50]. Indeed, the PD-linked VPS35(p.D620N) mutation displays a reduced ability to associate with the actin polymerizing WASH (Wiskott-Aldrich syndrome protein and SCAR Homology) complex [51][52][53] which leads to altered endosome-to-Golgi transport and autophagosome formation [54,44,55,56]. Perturbed function of the WASH complex is also implicated in hereditary spastic paraplegia [57].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups, including us, have noted that VPS35-retromer dysfunction has also been directly coupled to αSYN-related cytotoxicity. Retromer malfunction increases the lysosomal turnover of the mannose 6-phosphate receptor, thereby affecting the trafficking of cathepsin D (CTSD), a major lysosomal aspartyl protease that is involved in αSYN degradation (Follett et al 2014;Miura et al 2014). We found that the genetic ablation of Drosophila Vps35 not only induced the accumulation of the detergent-insoluble αSYN species in the central nervous system but also exacerbated both locomotor impairments and compound eye degeneration in human αSYN-transgenic flies .…”
Section: Membrane Trafficking Defect In Parkinson's Diseasementioning
confidence: 91%
“…WASH is recruited to retromer-positive endosomal subdomains via the interaction of the extended C-terminal tail of FAM21 with the retromer subunit VPS35 (Harbour et al, 2012;Jia et al, 2012). Interestingly, a mutation in VPS35 (D620N) (Vilariño-Güell et al, 2011;Zimprich et al, 2011) that is associated with earlyonset Parkinson's disease has been shown to diminish the interaction of the SHRC with VPS35 and impair vesicular trafficking from the late endosome (Follett et al, 2013;McGough et al, 2014;Zavodszky et al, 2014). Studies in Drosophila have recently shown important roles for WASH in regulating integrin receptor trafficking and lysosome acidification (Nagel et al, 2017).…”
Section: Jmymentioning
confidence: 99%